Sistem Pakar Mendiagnosa Penyakit Kanker Nasofaring Sejak Dini Menggunakan Metode Dempster Shafer Berbasis Web - Syukriadi Pulungan; M. Fakhriza; Aninda Muliani Harahap (Lembaga Pengembangan Kinerja Dosen, 2023)
Cancer is a condition that often threatens human health. Lack of public awareness of the main signs, symptoms, and causes of cancer is one of the factors causing the increasing mortality rate from the disease. Nasopharyngeal carcinoma is a cancer that affects humans and is potentially fatal. In Indonesia, where KNF is one of the top five malignant tumors with the most frequency, Nasopharyngeal Carcinoma (KNF) is the most malignant tumor among ENT malignant tumors (along with uterine cervical malignant tumors, breast tumors, lymph node tumors and skin tumors). ). The Dempster Shafer method is one of many techniques that can be used to diagnose nasopharyngeal carcinoma. The Dempster Shafer method is a mathematical approach to proofs that combines different bits of information (proofs) to estimate the probability of an event. It is based on the functions of trust and reasonable reasoning. Based on the description above, an expert system with the Dempster Shafer approach is needed that will help medical professionals and the general public in identifying the symptoms of Nasopharyngeal Carcinoma (KNF) early. So many people can identify diseases affecting the nasopharynx, especially the neck and head, with the help of this method and get immediate treatment.